Influence of thermal effects of fire on mechanical properties composite reinforcement - Kamlyuk Андрей; Shirko Алексей; Spiglazov Александр; Drobysh Антон (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
Experimentally investigated the mechanical and elastic properties of the composite reinforcement as under normal temperature conditions and when exposed to elevated temperatures. A model of the behavior of composite reinforcement, taking into account the temperature effect on its mechanical and elastic characteristics. Developed a database containing the temperature coefficients of the tensile strength and modulus of elasticity for the valves with different types of reinforcing filler.